2014
DOI: 10.1371/journal.pone.0100579
|View full text |Cite
|
Sign up to set email alerts
|

Hearts from Mice Fed a Non-Obesogenic High-Fat Diet Exhibit Changes in Their Oxidative State, Calcium and Mitochondria in Parallel with Increased Susceptibility to Reperfusion Injury

Abstract: RationaleHigh-fat diet with obesity-associated co-morbidities triggers cardiac remodeling and renders the heart more vulnerable to ischemia/reperfusion injury. However, the effect of high-fat diet without obesity and associated co-morbidities is presently unknown.ObjectivesTo characterize a non-obese mouse model of high-fat diet, assess the vulnerability of hearts to reperfusion injury and to investigate cardiac cellular remodeling in relation to the mechanism(s) underlying reperfusion injury.Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 80 publications
(103 reference statements)
6
51
0
1
Order By: Relevance
“…The proposed mechanism for increased I/R injury was a combination of elevated catalase level and inability to adapt to an increase in oxidative stress, fragmentation of mitochondria, reduced mitochondrial density and elevated diastolic [Ca 2+ ] i [1]. In this study we show for the first time that switching the diet from high-fat back to normal for a few weeks significantly reduces the vulnerability of isolated hearts to I/R.…”
Section: Discussionmentioning
confidence: 70%
“…The proposed mechanism for increased I/R injury was a combination of elevated catalase level and inability to adapt to an increase in oxidative stress, fragmentation of mitochondria, reduced mitochondrial density and elevated diastolic [Ca 2+ ] i [1]. In this study we show for the first time that switching the diet from high-fat back to normal for a few weeks significantly reduces the vulnerability of isolated hearts to I/R.…”
Section: Discussionmentioning
confidence: 70%
“…Several reports have demonstrated that HF45% diet increases the body weight gain (Huang et al, ; Turdi et al, ; Carrer et al, ; Zhang et al, ; Hua et al, ; Noyan‐Ashraf et al, ). However, another study showed that HF45% did not increase the body weight gain when compared to mice fed control diet (Littlejohns et al, ). Similarly, we found that HF45% diet was not able to increase the body weight in relation to LF diet‐fed mice.…”
Section: Discussionmentioning
confidence: 97%
“…We also observed mitochondrial genes to be up-regulated only in the livers of the mice in the reversal group. Mitochondrial dysfunction has been observed in obese and diabetic individuals and in HF diet-fed mice (45)(46)(47). The reversion of HFD to low fat diets in mice can result in reversion of some mitochondrial defects observed in heart cells (48).…”
Section: Discussionmentioning
confidence: 99%